Is REDD+ an idea whose time has come, or gone? - Sunderlin, William D.; Atmadja, S. (Center for International Forestry Research, 2009)
Previous international and national policies have, for various reasons, failed to prevent deforestation in developing countries. REDD+ incorporates some of these past policies, but also some innovations. Lessons from past experience will need to be taken on board and new alliances will need to be forged if REDD+ is to be successful.